2017
DOI: 10.4236/jamp.2017.54084
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Study of Vertebral Compression Fracture Using Finite Element Analysis

Abstract: This research aimed to mechanically analyze vertebral stress concentration in one healthy subject and one subject with osteoporotic first lumbar (L1) vertebral compression fracture by using finite element analysis (FEA). We constructed three-dimensional image-based finite element (FE) models (Th12L2) by using computed tomographic (CT) digital imaging and communications in medicine (DICOM) for each patient and then conducted exercise stress simulations on the spine models. The loadings on the 12th thoracic vert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The spine segment was loaded increasingly from 0 N to 2000 N, at room temperature, because a series of biomechanical studies were conducted at values between 2 and 14 kN [ 6 , 7 , 8 ]. The resulting data are represented by the load–displacement pair points collected by means of the data acquisition system of the test machine.…”
Section: Methodsmentioning
confidence: 99%
“…The spine segment was loaded increasingly from 0 N to 2000 N, at room temperature, because a series of biomechanical studies were conducted at values between 2 and 14 kN [ 6 , 7 , 8 ]. The resulting data are represented by the load–displacement pair points collected by means of the data acquisition system of the test machine.…”
Section: Methodsmentioning
confidence: 99%
“…Following fracture, creep deformation of the fractured vertebral body significantly increased, especially in the anterior region, and similar changes were observed at the adjacent level. In addition, Takano et al 35 revealed that vertebral fracture increased stress concentration in the affected vertebrae and the adjacent vertebrae using finite element analysis. These results suggest that AVF is caused not only by bone fragility but also by the increase in stress concentration in the adjacent vertebrae.…”
Section: Discussionmentioning
confidence: 99%
“…Finite element modeling can provide a practical understanding of compression injuries of different patient types. Takano et al used modeling to analyze the vertebral stress concentration of a healthy subject compared to an individual with an osteoporotic L1 vertebral compression fracture [ 20 ]. Under five basic vertebral physiologic motions, higher stress, and the strain exhibited by the osteoporotic subject, finite element analysis provides a useful method to evaluate injury patterns of the spine and a comprehensive understanding of each patient’s condition, which is crucial in determining the best surgical treatment.…”
Section: Reviewmentioning
confidence: 99%